Manufacture and Use of Lapita Conus Multi-Segment Broad Rings: Evidence from the Teouma site, Central Vanuatu. (2nd July 2020) - Langley, Michelle C.; Bedford, Stuart; Spriggs, Matthew; Phillip, Iarawoi
Abstract: Material culture associated with the Lapita Cultural Complex has been commented on for more than 100 years. Discussion and focus, however, have overwhelmingly concentrated on the distinctive dentate-stamped pottery. In this paper we highlight a very particular shell artifact form, examples of which were found in burial contexts at the Teouma Lapita site, Efate, Vanuatu. Here termed Conus Multi-Segment Broad Rings, each ring consists of three to four broad sections or segments that were joined via drilled perforations and threads. As only isolated segments of this ornament type are usually recovered from the archaeological record, an understanding of their finished form and use life has previously been lacking. Found across the Lapita distribution and associated only with this period, Conus Multi-Segment Broad Rings appear to be a stylistic marker additional to the dentate-stamped pottery. Here we reconstruct the manufacture and use of this distinctive shell ornament type through examination of the micro-trace evidence observed on the Teouma artifacts, as well as experimental working of modern Conus shell.